The Internalization of Tafaqquh Fiddin Values through Tafsir Studies: (A Case Study at Persis 84 Ciganitri Islamic Boarding School) - Puji Purwati (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
This study uses descriptive qualitative methods to explore the internalization of the value of Tafaqquh Fiddin in the Persis 84 Ciganitri Islamic Boarding School. This study found that Tafaqquh Fidiin, as the spirit of Q.S At-Taubah verse 122, is the principal value of Education revived in all learning activities in Islamic Boarding Schools. The results of this study show that the concept of Tafaqquh Fiddin at the Persis 84 Ciganitri Islamic Boarding School in the learning process is reflected in the content of the religious curriculum and takhasus, the study of the book of tafsir, and the essence of Tafaqquh Fiddin is not only in the understanding of the students but at the same time how it goes hand in hand with deeds. The process of internalizing the value of Tafaqquh Fiidin through the study of the book of tafsir at the Persis 84 Ciganitri Islamic Boarding School through 3 stages: cognitive understanding, Affection or emotional acceptance, and behaviour change. Tafaquh fiddin is accepted as a value that students revive through studying the book of tafsir. The impact of the Internalization of Tafaqquh fiddin through the study of the book of tafsir includes changes in subjective reality and self-identity, namely students are inspired to become mufassir, students can make written works of tafsir, and students can read tafsir from the source of their book of tafsir, so from the internalization of Tafaqquh fiddin through the study of the book of tafsir becomes a manifestation of the effort to give birth to the generation of thaifah liyataffaqahu fiddin which is desired in Q.S At-Tauabah verse 122.